Physiological responses and transcriptomic changes reveal the mechanisms underlying adaptation of Stylosanthes guianensis to phosphorus deficiency - Chen, Zhijian; Song, Jianling; Li, Xinyong; Arango, Jacobo; Cardoso, Juan Andrés; Rao, Idupulapati M.; Schultze-Kraft, Rainer; Peters, Michael; Mo, Xiaohui; Liu, Guodao (Springer, 2021)
Background: Phosphorus (P) is an essential macronutrient for plant growth that participates in a series of biological processes. Thus, P deficiency limits crop growth and yield. Although Stylosanthes guianensis (stylo) is an important tropical legume that displays adaptation to low phosphate (Pi) availability, its adaptive mechanisms remain largely unknown. Results: In this study, differences in low-P stress tolerance were investigated using two stylo cultivars (‘RY2’ and ‘RY5’) that were grown in hydroponics. Results showed that cultivar RY2 was better adapted to Pi starvation than RY5, as reflected by lower values of relative decrease rates of growth parameters than RY5 at low-P stress, especially for the reduction of shoot and root dry weight. Furthermore, RY2 exhibited higher P acquisition efficiency than RY5 under the same P treatment, although P utilization efficiency was similar between the two cultivars. In addition, better root growth performance and higher leaf and root APase activities were observed with RY2 compared to RY5. Subsequent RNA-seq analysis revealed 8,348 genes that were differentially expressed under P deficient and sufficient conditions in RY2 roots, with many Pi starvation regulated genes associated with P metabolic process, protein modification process, transport and other metabolic processes. A group of differentially expressed genes (DEGs) involved in Pi uptake and Pi homeostasis were identified, such as genes encoding Pi transporter (PT), purple acid phosphatase (PAP), and multidrug and toxin extrusion (MATE). Furthermore, a variety of genes related to transcription factors and regulators involved in Pi signaling, including genes belonging to the PHOSPHATE STARVATION RESPONSE 1-like (PHR1), WRKY and the SYG1/PHO81/XPR1 (SPX) domain, were also regulated by P deficiency in stylo roots. Conclusions: This study reveals the possible mechanisms underlying the adaptation of stylo to P deficiency. The low-P tolerance in stylo is probably manifested through regulation of root growth, Pi acquisition and cellular Pihomeostasis as well as Pi signaling pathway. The identified genes involved in low-P tolerance can be potentially used to design the breeding strategy for developing P-efficient stylo cultivars to grow on acid soils in the tropics.